SIMULATION ANALYSIS AND IMPROVEMENT FOR PEDESTRIAN PROTECTION FLEX LEG - WANG ShengBo; LIU Gang; HUANG XiaoYing; GE HongJian; MA HuiZhen (Jixie qiangdu)
In order to export the vehicles to ASEAN smoothly, according to the needs of new vehicle research and development, aiming at meeting the limit value of leg protection under ASEAN-NCAP, a flexible leg (Flex-PLI) collision finite element model is built and calculated. Aiming at the problems in the vehicle design, an improved scheme was proposed and verified by simulation to be feasible. Finally, a full score was obtained through the actual vehicle test. The test results verified the reliability of the simulation, accumulated experience for the development of pedestrian calf protection.